2022
DOI: 10.2337/figshare.19182023.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancement of Impaired Olfactory Neural Activation and Cognitive Capacity by Liraglutide, but not Dapagliflozin or Acarbose, in Patients With Type 2 Diabetes: A 16-Week Randomized Parallel Comparative Study

Abstract: <b>Objective:</b> <a></a><a>The comparative neuroprotective effects of different anti-diabetic drugs have not been characterized in randomized controlled trials. Here, </a><a>we investigated the therapeutic effects of liraglutide, dapagliflozin, or acarbose treatment on brain functional alterations and cognitive changes in patients with type 2 diabetes.</a> <p> </p> <p><b>Research design and methods: </b>Thirty-six patients with ty… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nauck, M (14) found that after the addition of sitagliptin to the treatment regimen of patients with diabetes with poor glucose control on oral antidiabetes drugs, it was found that the standard deviation of 24-h glucose, the 24-h mean glucose fluctuation range, and the glucose fluctuation range of patients decreased significantly.GLP-1 signaling in the central nervous system can control glucose uptake and production in peripheral tissues, and dulaglutide also plays a role through GLP-1 receptor signaling pathway (23), which may be similar to DPP4 inhibitors in keeping glucose stable. Recent studies suggest that GLP-1 acting can directly effect the brain's feeding center, affecting the perception of the reward value of food (24). The activation of GLP-1 receptors in the human brain helps to regulate appetite and food reward (25,26).…”
mentioning
confidence: 99%
“…Nauck, M (14) found that after the addition of sitagliptin to the treatment regimen of patients with diabetes with poor glucose control on oral antidiabetes drugs, it was found that the standard deviation of 24-h glucose, the 24-h mean glucose fluctuation range, and the glucose fluctuation range of patients decreased significantly.GLP-1 signaling in the central nervous system can control glucose uptake and production in peripheral tissues, and dulaglutide also plays a role through GLP-1 receptor signaling pathway (23), which may be similar to DPP4 inhibitors in keeping glucose stable. Recent studies suggest that GLP-1 acting can directly effect the brain's feeding center, affecting the perception of the reward value of food (24). The activation of GLP-1 receptors in the human brain helps to regulate appetite and food reward (25,26).…”
mentioning
confidence: 99%